POTENSI TUMBUHAN LOKAL SEBAGAI AGEN FITOREMEDIASI UNTUK MENURUNKAN KADAR LOGAM MERKURI (Hg) PADA LAHAN BEKAS PENAMBANGAN EMAS TANPA IZIN DI KABUPATEN SAROLANGUN, JAMBI - Fatur Rahman; Freddy Ilfan; Zuli Rodhiyah; Mahya Ihsan (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
Illegal Gold Mining (PETI) is activity of gold mining by gold miners have not license. The negative impacts PETI is mercury contamination. The efforts minimize mercury contamination by phytoremediation. This research aimed to discover local plants have potential reducing mercury (Hg) contamination. This research used purposive sampling technique and conducted in Monti Village, Sarolangun, Jambi. Inventory plants obtained 14 species specifically, Macaranga sp., Paspalum sp., Trema tomentosa, Imperata cylndrica, Lophatherum sp., Eleusine sp., Molineria sp., Lycopodium sp., Gleichenia linearis, Ipomea sp., Scleria sp., Eleocharis interstincta, Melastoma sp., and Phragmites sp. 14 plants, three plants dominated particularly, Phragmites sp. (37.35%), Melastoma sp. (30.64%), and Eleocharis interstincta (25.41%). Phragmites sp. have BAC values ​​(0.381), BCF (0.606), TF (0.628), Melastoma sp. have BAC values ​​(0.170), BCF (0.333), TF (0.511), and Eleocharis interstincta have BAC values ​​(0.245), BCF (0.441), TF (0.555). The calculation result BAC, BCF and TF obtained Phragmites sp. have hight values.